2011
DOI: 10.1038/jhg.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Support for association between the Ser205Leu polymorphism of p75NTR and major depressive disorder

Abstract: Altered neurotrophin functions have been implicated in major depressive disorder (MDD). Previously, we reported an association between MDD and a missense polymorphism (Ser205Leu: rs2072446) of the gene encoding the p75 neurotrophin receptor (p75 NTR ). However, contradictive negative results have also been reported. This study tried to replicate the association in an independent sample. Subjects were 668 patients with MDD and 1130 healthy controls. The proportion of individuals carrying the Leu205 allele was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…This SNP has been suggested to exert a protective effect against the development of MDD in a cohort of female Japanese subjects. 27 Our data suggest no association between this SNP and depressive symptoms in either HIV positive or negative women. However, the genetic background of our samples differs from those used in previous studies, as does our definition of “depressed”, which was not based on a clinical diagnosis of MDD.…”
Section: Discussioncontrasting
confidence: 48%
“…This SNP has been suggested to exert a protective effect against the development of MDD in a cohort of female Japanese subjects. 27 Our data suggest no association between this SNP and depressive symptoms in either HIV positive or negative women. However, the genetic background of our samples differs from those used in previous studies, as does our definition of “depressed”, which was not based on a clinical diagnosis of MDD.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast, the SerSer variant of the Ser205Leu polymorphism, a variant with a conserved receptor structure (Fujii et al, 2011;Gau et al, 2008), showed low viral loads and elevated liver enzyme activity levels in moderate/severe inflammation, suggesting that the wild-type p75 NTR pathway favors liver injury in individuals with advanced stages of inflammatory activity, as shown in different cell lines in which the p75 NTR pathway stimulates the production of proinflammatory cytokines that contribute to chronic tissue injury (Minnone et al, 2017;Elshaer and El-Remessy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The change in the peptide is related to structural changes, cellular localization and receptor signaling (Cohen-Cory et al, 1991;Drysdale et al, 2000). This SNP is associated with depressive disorder in Japanese women (Fujii et al, 2011) and Alzheimer's disease (Lester et al, 2012), and the Leu variant has a protective role against the development of these disorders, although heterozygous patients have a weaker response to antidepressants than do patients homozygous for Ser +/+ (Gau et al, 2008). The selection of SNPs representative of haplotypes (tag SNPs) is being used as a way of representing the biological significance of the genetic variations of p75 NTR (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The two polymorphisms located in NGFR, rs734194 and rs2072446, have been previously reported to be involved in major depressive disorder and Alzheimer's disease (Cheng et al, 2012;Cozza et al,2008;Fujii et al, 2011). Neurotrophic factors (NF) such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) are involved in axon growth, dendrite pruning and the expression of proteins crucial for normal neuronal function, such as neurotransmitters and ions channels (Huang and Reichardt, 2001).…”
Section: Discussionmentioning
confidence: 99%